2010
DOI: 10.1021/ac902650w
|View full text |Cite
|
Sign up to set email alerts
|

Elemental Bio-imaging of Thorium, Uranium, and Plutonium in Tissues from Occupationally Exposed Former Nuclear Workers

Abstract: Internal exposure from naturally occurring radionuclides (including the inhaled long-lived actinides (232)Th and (238)U) is a component of the ubiquitous background radiation dose (National Council on Radiation Protection and Measurements. Ionizing radiation exposure of the population of the United States; NCRP Report No. 160; NCRP: Bethesda, MD, 2009). It is of interest to compare the concentration distribution of these natural alpha-emitters in the lungs and respiratory lymph nodes with those resulting from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 20 publications
0
24
0
Order By: Relevance
“…It will be interesting to analyse similar thoria samples using fsand ps-lasers by those laboratories having access to these systems and obtain a comparison of the results of ns-versus ps-and fs-lasers in view of the studies reported for determination of thorium at trace to ultra-trace levels by LA-ICP-MS [13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…It will be interesting to analyse similar thoria samples using fsand ps-lasers by those laboratories having access to these systems and obtain a comparison of the results of ns-versus ps-and fs-lasers in view of the studies reported for determination of thorium at trace to ultra-trace levels by LA-ICP-MS [13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…20 Our laboratory has applied this technique to the imaging of trace elements in mouse brains, 21 osteoarthritic joints 22 and human lymphatic tissues. 23,24 LA-ICP-MS is a relatively simple technique that does not require a high vacuum ion source or suffer from severe matrix effects. Complicated and often hazardous digestion procedures are not required as it is a solid-state analyzer.…”
Section: La-icp-msmentioning
confidence: 99%
“…LA-ICP-MS was used to study uranium (U), plutonium (Pu) and thorium (Th) exposure in lymphatic tissue from ex-nuclear workers years after suffering acute occupational exposures [20], and background levels of Th and U in human hippocampus tissue was proposed as a possible internal standard for measuring endogenous metals in tissue [21], though this approach fails to meet contemporary guidelines for internal standardization for LA-ICP-MS due to each element's extremely low abundance [17,22]. …”
Section: Imaging Biological Exposuresmentioning
confidence: 99%